Talking About Professionalism Through the Lens of Professional Identity. Issue 1 (4th December 2018) - Iserson, Kenneth V.
Abstract: Professionalism is one of the Accreditation Council for Graduate Medical Education's (ACGME) Core Competencies, but the breadth of its content often makes this a difficult topic, both in remedial counseling and when presenting the topic to medical trainees and practicing clinicians. Physician professionalism encompasses both clinical competence and the virtues that comprise the physician's social contract. This difficult subject may best be approached tangentially, through the lens of professional identity. Professional identity describes clinicians' affinity for, acculturation into, and identification with the practice of medicine. One method to highlight the benefits that individuals accrue by adopting professionalism's elements is to pose questions that optimize listeners' self‐reflection about their lives and aspirations—in essence, their professional identity. Discussing professionalism this way often yields in‐depth discussions of how trainees believe their professional identity was formed and will impact their long‐term goals. Both in teaching and in counseling, educators can frame their discussions using professionalism and professional identity's overlapping and reinforcing elements to show listeners how to advance their personal and professional goals and avoid the short‐ and long‐term consequences of unprofessional behavior. To engage the audience, educators and supervisors can emphasize how adhering to the elements of professionalism may determine their career opportunities, the professional respect they receive, and their career fulfillment and, ultimately, longevity. In this way, educators can better guide trainees and clinicians to understand their personal reasons for acting professionally, that is, doing the right thing, at the right time, in the right way, and for the right reason.